2022
DOI: 10.3389/fpubh.2022.1055699
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between functional disability and multimorbidity among middle-aged and older adults in Thailand

Abstract: ObjectivesThe purpose of this study was to assess the bidirectional association between multimorbidity (MM) and functional disability among middle-aged and older adults in a longitudinal study in Thailand.MethodsWe analyzed longitudinal data of participants aged 45 years and older from two consecutive waves (in 2015 and 2017) of the Health, Aging, and Retirement in Thailand (HART). Functional disability was assessed with a 4-item activity of daily living (ADL) scale. Logistic regression analysis was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…With regard to physical function, we found that multimorbidity was significantly associated with an increased risk of disability, which was consistent with previous research studies ( Quiñones et al, 2016 , 2018 ; Wei et al, 2018 ; Pengpid et al, 2022 ). We also found that the “cardio-metabolic” and “multisystem morbidity” classes were associated with a higher risk of disability, which is consistent with previous studies showing a positive association of metabolic multimorbidity with a higher risk of disability ( Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to physical function, we found that multimorbidity was significantly associated with an increased risk of disability, which was consistent with previous research studies ( Quiñones et al, 2016 , 2018 ; Wei et al, 2018 ; Pengpid et al, 2022 ). We also found that the “cardio-metabolic” and “multisystem morbidity” classes were associated with a higher risk of disability, which is consistent with previous studies showing a positive association of metabolic multimorbidity with a higher risk of disability ( Zhao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although previous research used different classifications for the Barthel Index, for the current study, any participant with a score less than 100 was considered as having disability as this approach has been used in prior research using disability scales on community-dwelling older adults. [36][37][38][39] In the current study, we found that individuals with MLTC (those with ≥2 chronic diseases) are 2.5 times more likely to fall than those without a chronic disease. This is consistent with earlier reports by Yan et al 45 and You et al 46 Yan et al reported that patients with two, and ≥3 chronic diseases had an 85%, and 175% increased risk of falls, respectively, compared with older adults without chronic conditions.…”
Section: Discussionsupporting
confidence: 48%
“…This approach has been used in prior research using disability scales on community-dwelling older adults. [36][37][38][39] The validity and reliability of the BI was established for geriatric populations 40 and languages. [41][42][43] At the time of the study, no Arabic version of the BI was available.…”
Section: Falls Efficacy Scale International (Fes-i)mentioning
confidence: 99%
“…Chronic conditions were assessed by (self-reported) healthcare provider diagnosis: ‘(1) hypertension, (2) diabetes, (3) cardiovascular diseases, heart disease and heart failure, (4) rheumatism, arthritis, bone diseases and osteoporosis, (5) kidney diseases, (6) brain diseases and psychiatric problems and (7) lung diseases/emphysema’. 31 …”
Section: Methodsmentioning
confidence: 99%